2019
DOI: 10.3389/fnins.2019.01043
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Candesartan Alone and Its Combination With Estrogen on Post-traumatic Brain Injury Outcomes in Female Rats

Abstract: Aim: The aim of this study was to evaluate the effect of candesartan (angiotensin II type I receptor blocker) alone and its combination with estrogen on the changes in brain edema, intracranial pressure (ICP), and cerebral perfusion pressure (CPP) following diffuse traumatic brain injury (TBI) in female rats.Methods: TBI was induced in ovariectomized female rats using Marmarou's method. The treatment groups received low-dose (LC) and high-dose (HC) candesartan, estrogen (E2), a combination of estrogen vehicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Previous studies have reported that candesartan, one of the angiotensin receptor blockers, could reduce lesion volume and improve motor and memory function after traumatic brain injury in mice ( Villapol et al, 2012 ; Hajmohammadi et al, 2019 ; Attilio et al, 2021 ), however, the molecular mechanism is still poorly understood. To gain insight into the potential molecular basis of this drug, we conducted an integrative analysis of single-cell (GEO accession: GSE101901) and bulk RNA-seq data ( Attilio et al, 2021 ) (GEO accession: GSE163415) to analyze the cell-type-specific changes in gene expression patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that candesartan, one of the angiotensin receptor blockers, could reduce lesion volume and improve motor and memory function after traumatic brain injury in mice ( Villapol et al, 2012 ; Hajmohammadi et al, 2019 ; Attilio et al, 2021 ), however, the molecular mechanism is still poorly understood. To gain insight into the potential molecular basis of this drug, we conducted an integrative analysis of single-cell (GEO accession: GSE101901) and bulk RNA-seq data ( Attilio et al, 2021 ) (GEO accession: GSE163415) to analyze the cell-type-specific changes in gene expression patterns.…”
Section: Resultsmentioning
confidence: 99%
“…After removal of duplicates, a total of 5629 articles remained to be screened based on title and abstract. Full-text assessment of 116 studies yielded 20 studies which met the inclusion criteria [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] . Excluded studies are detailed in Figure 1 and Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…After the induction of diffuse TBI, the rats were immediately connected to the animal respiratory pump (TSA respiratory compact, Bad Homburg, Germany). After spontaneous breathing, the rats were detached from the ventilator and returned to their cage [26].…”
Section: Induction Of Diffuse Traumatic Brain Injury (Tbi)mentioning
confidence: 99%